23400 = 1260t - 16t^2
16t^2 - 1260t + 23400 = 0
4(4t^2 - 315t + 5850) = 0
4t^2 - 315t + 5850 = 0
(t - 30)(4t - 195) = 0
t = 30 or (195/4)
ANS : 30 or 48.75
2006-09-30 05:58:28
·
answer #1
·
answered by Sherman81 6
·
0⤊
0⤋
23400 = 1260t - 16t^2 (Put all terms on left)
16t^2 - 1260t + 23400 = 0 (Factor out 4)
4(4t^2 - 315t + 5850) = 0
(2t - 60)(2t - 97.5)
2((t - 30)(t - 48.75))
t = 30 or t = 48.75
QED
2006-09-30 17:03:53
·
answer #2
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
simplest technique is using direct formula::
at^2+bt+c=0;
t={ -b(+/-) (b^2-4ac)^1/2 } / 2a
here, a=16,b= -1260,c=23400
2006-09-30 02:10:37
·
answer #3
·
answered by ravi 1
·
0⤊
0⤋
simply use quadratic solving method dear...
first remove common figure outside brackets...
put two brackets
find 4 ideal numbers
cross multiply and put in brackets.
2006-09-30 08:09:15
·
answer #4
·
answered by sweetfloss8 2
·
0⤊
0⤋
I would sit down, think, scribble the calculations and figure it out.
2006-09-30 02:04:40
·
answer #5
·
answered by Signilda 7
·
0⤊
1⤋
you need to use the cuadratic formula...
2006-09-30 02:05:13
·
answer #6
·
answered by J C 1
·
0⤊
0⤋